Latin American migrations to the U.S. Heartland : changing social landscapes in Middle America - Allegro, Linda; Wood, Andrew Grant, 1958- (Working class in American history., 2013)
Responding to inaccuracies concerning Latino immigrants in the United States as well as an anti-immigrant strain in the American psyche, this collection of essays examines the movement of the Latin American labor force to the central states of Oklahoma, Kansas, Nebraska, Arkansas, Missouri, and Iowa.